Laser-Assisted Fabrication of Nanostructured Substrate Supported Electrodes for Highly Active Supercapacitors - Asghar, Mamoon; Zahra, Syedah Afsheen; Khan, Zarah; Ahmed, Momina; Nasir, Farheen; Iqbal, Mudassir; Mohammad, Mohammad Ali; Mahmood, Asif; Akinwande, Deji; Rizwan, Syed (Frontiers in Materials, 2020)
Supercapacitors (SCs) have attracted great attention as renewable energy storage devices due to high power densities and cost effectiveness. In this work, a one-step method is reported to fabricate the Laser scribed SC using laser reduced Polyimide (LRPI) electrodes as a substrate. An Iono-gel polymer electrolyte based on polyvinyl alcohol, potassium hydroxide and 1-Butyl-3-methyl imidazolium Bromide ([Bmim]Br) was utilized because of its wider voltage window, good ionic conductivity and better adhesion with electrode material. The assembled device exhibited an excellent specific capacitance of 2.19 mFcm-2 at a maximum current density of 0.263 mAcm-2. The energy density is measured to be 1.21 µWhcm-2 that is much higher than usual capacitor. Given these electrochemical properties, cost effective one-step method and scalable approach provide a strategy to fabricate lightweight, stretchable and flexible supercapacitors for future microscale energy storage devices i.e. flexible displays, electrical sensors and wearable electronics.